Challenges in remote mathematics teaching during the covid-19 pandemic: a systematic literature review - Saeger, Márcia Maria de Medeiros Travassos (2024)
The COVID-19 pandemic gave rise to the need for social isolation, causing the closing of schools, which, in order not to stop their activities, adhered to the remote teaching format. This format required a reconfiguration of classes and teaching methodologies adopted by teachers, bringing, consequently, numerous challenges. In this context, this research aimed to identify the challenges faced by teachers for remote teaching of Mathematics during the COVID-19 pandemic. Therefore, a Systematic Literature Review was carried out in articles published between 2020 and 2021. Data were analyzed using a quantitative approach. As results, it was evident that the Mathematics teachers used several tools for remote teaching, the most recurrent being the videoconference platforms, the WhatsApp application and video classes on YouTube.